Kampo Medicines for Frailty in Locomotor Disease - Nakae, Hajime; Hiroshima, Yuko; Hebiguchi, Miwa (Frontiers in Nutrition, 2018)
Frailty is a syndrome that includes broad problems of senility and consists of three domains: physical, psychological, and social. Kampo medicine is used for intervention in cases of hypofunction in a mental or physical state. Kampo treatment, using Hojin formulations such as Hachimijiogan and Gosyajinkigan, is useful in patients with “jinkyo”, or kidney hypofunction. Ketsu includes both blood and its metabolic products that circulate throughout the body. Oketsu is a disturbance of ketsu and is considered to be a microcirculation disorder. Anti-oketsu formulations, such as Keishibukuryogan and Jidabokuippo, are useful in the treatment of trauma patients who are experiencing swelling and pain. “Ki” is the universal energy that exists in the world. Hoki formulations, such as Rikkunshito and Hochuekkito, are useful in patients with poor appetites for reinforcing vital energy. Juzentaihoto and Ninjinyoeito are useful in patients with hypofunction of ki and ketsu, which are accompanying symptoms of coldness or cutaneous dryness. Thus, Kampo medicines can be used as a superior approach for the management of frailty.